Demand factors for international tourism in Malaysia: 1998-2009 - Ahmad Kosnan, Siti Shuhada; Ismail, Normaz Wana; Kaniappan, Shivee Ranjanee (2012)
This study extend Ismail and Samdin (2010) works on demand factors in Malaysian tourism industry uses the Gravity type approach for the panel data spanning from 2002 – 2010. The dependent variable uses in the model is tourist receipt in Malaysia from twenty nine countries. This study finds that the market size for both destination and source countries, country that sharing border and common language with Malaysia are increases inbound tourist to Malaysia. On the other hand, the shorter the distance, the lower transportation cost, can also attract more tourists. This study also reveal that the role of exchange rate and the cost of living are equally important as a depreciation of Ringgit Malaysia (RM) and lower in the cost of living attract more tourists in Malaysia. Outcome of this research can be used among policy makers to guide future managements of Malaysian tourism industry.